Three main components for Ulul Albab teachers' professional development programme theory - Subirim @ Subirin, Nor Adzimah; Alwi, Nor Hayati; Mohd Fakhruddin, Fathiyah; Abdul Manaf, Umi Kalthom; Salim, Siti Suria; Hassan, Siti Aishah; Othman, Shamsudin; Mohd Ali, Nurul Jawahir (Human Resource Management Academic Research Society, 2018)
The role of teachers as purveyors of knowledge and values is crucial to improve the quality of educational processes which leads to the excellence outcomes. The quality of education directly needs the teachers to play their roles. Therefore, the curriculum of education and preparation of teachers should be considered as the central and most crucial in the reconstruction of any educational system. In the context of Ulul Albab, objectives, mission and vision have been drawn up beautifully to achieve the aim of having a generation who is able to use their mind and heart to understand the essence of life based on strong foundation of Al-Quran epistemology. It is therefore, the students of Ulul Albab program that need to be educated, guided, facilitated, and monitored properly to prepare them as Ulul Albab generation. Hence, teachers are expected to play their role as a group who will be responsible to assist these students. This research has been concerned on teachers of the Ulul Albab program as the key implementer of Ulul Albab curriculum. The purpose of this research is to examine the components of professional development (PD) theory for teachers of Ulul Albab program regardless of field of expertise, religious or academic. Six experts and prominence in various fields have been interviewed from purposeful sampling method, in order to investigate the relevancy of developing teachers’ professional development for Ulul Albab teachers. Open coding grounded theory approach by using Qualitative Data Analysis (QDA) Software Atlas ti has been chosen to analyse the data, whereby, the theory develops from the data as it is collected and analysed inductively. In-depth interview method has been using for collecting data and the recorded interviews were transcribed verbatim. The findings have shown that there are three main components; the Input, the Process/Mechanism and the Outcome in which several elements have been drawn up from the findings such as the selection of the right teachers, teachers’ training (pre-service and in-service) model, and the nature of Ulul Albab teachers. Each component that represents every element in the findings will be treated as the foundation in developing Ulul Albab Teachers’ Professional Development Programme Theory. From the discussion, the experts collaboratively agree that teachers’ professional development is necessary to prepare teachers with certain characteristics. In a nutshell, it is crucial to train the teachers with a systematic and dynamic professional development according to the concept of Ulul Albab, for the sake of moulding future generation that would be the frontliner of Muslim civilization in the country.